Establishment and characterization of meningioma patient-derived organoid. (December 2021) - Chan, Henry Siu Cheung; Ng, Ho Keung; Chan, Aden Ka-Yin; Cheng, Sau Ha; Chow, Chit; Wong, Nathalie; Wong, George Kwok Chu
Highlights: Meningioma cells could grow and proliferate under in vitro 3D culture condition. Morphology under 3D culture condition was different in different time points. Organoid culture is applicable for meningioma studies. Abstract: Meningioma is a central nervous system tumor originated from arachnoid cells. 2D cell culture is widely used as a platform for tumor research as it enables us to culture cells in in vitro and a controlled environment. However, in 2D culture condition, 3D architecture of in vivo tumor mass is lost and phenotypic change may occur. Due to the drawbacks of 2D cell culture, organoid culture is seen as an alternative platform for disease modeling, drug testing and personalized medicine. The objective of this study was to establishing protocol for culturing cells from patient meningioma tissue in in vitro 3D environment. Eight meningiomas were collected for the 3D organoid culture. Cells of 5 meningioma tissues survived and proliferated. Under 3D culture condition, cell aggregates were formed and cytoplasmic processes linking the cell aggregates could be observed. In H&E staining, ovaloid cells and spindle cells were observed. Resembling cultured organoids observed under the light microscope, cell aggregates were also observed in the H&E staining. Epithelial Membrane Antigen (EMA) staining was positive. In 4 (80%) cultured organoids, low Ki67 index (≤6%) were measured. In one cultured organoid, a high Ki67 index (12.8%) was seen. The result of this study revealed the feasibility of culturing meningioma cells in in vitro 3D culture condition. Organoid technology showed its potential as an alternative platform for meningioma research.